Case-Based PowerPoint to Improve Knowledge and Comfort of Having Code Status Discussions by Physician Assistant and Nurse Practitioner Students. Issue 4 (October 2019) - Schoonover, Kimberly; Herber, Andrew; Heusinkvelt, Sally; Yadav, Hemang; Burton, M. Caroline
Background: Little is known about how certain educational interventions may improve informed code status discussions by physician assistant (PA) and nurse practitioner students. Methods: This is a prospective, prospective, single academic center pilot study utilizing a short case-based PowerPoint that reviewed the differences between code status choices and the likelihood of survival to hospital discharge of attempted resuscitation after a cardiac arrest. Training occurred between September 1, 2017, and May 31, 2018. The study population included PA and adult gerontology acute care nurse practitioner (AGACNP) students during their inpatient internal medicine rotation (n = 9) and preclinical PA students (n = 5). Results: After training, there was a significant increase in knowledge in the likelihood of survival to hospital discharge ( P = .01) and comfort level in having an informed code status discussion (3.36 ± 0.81 vs 4.10 ± 0.80, P = .02). For questions related to identification of the correct code status, there were no significant differences before and after the intervention. Conclusion: A short case-based PowerPoint viewed by PA and AGACNP students increased the knowledge about the likelihood of survival to hospital discharge of attempted resuscitation after a cardiac arrest and increased the comfort level of having code status discussions with patients by PA and AGACNP students.